Swiss Programme for Research on Global Issues for Development (r4d programme) - NFP [Nr.] (2018)
Research and innovation are decisive factors for sustainable global development. With their knowledge, skills, experience and worldwide network of partners, researchers can make an important contribution towards the solution of global problems.